Cartilage lesions and ankle osteoarthrosis: review of the literature and treatment algorithm, - Alexandre Leme Godoy Santos; Marco Kawamura Demange; Marcelo Pires Prado; Tulio Diniz Fernandes; Pedro Nogueira Giglio; Beat Hintermann (Revista Brasileira de Ortopedia, 2014)
The main etiology of ankle osteoarthrosis is post-traumatic and its prevalence is highest amongyoung individuals. Thus, this disease has a great socioeconomic impact and gives rise to significant losses of patients' quality of life. The objective of its treatment is to eliminate pain and keep patients active. Therefore, the treatment should be staged according to the degree of degenerative evolution, etiology, joint location, systemic condition, bone quality, lower-limb alignment, ligament stability and age. The treatment algorithm is divided into non-surgical therapeutic methods and options for surgical treatment. Joint preservation, joint replacement and arthrodesis surgical procedures have precise indications. This article presents a review on this topic and a proposal for a treatment algorithm for this disease.